Humanoid Robot With Surveillance And Virtual Voice Assistance - et. al., Neethu K N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Humanoid robots are those resemblance of their motion and functioning similar to human beings, having capabilities of doing day to day activities similar to man and replace him in every possible way. These activities vary from daily activities such as walking, standing, to staircase climbing, running, and kneeling. The main purpose of this project is to build a personal assistance which resembles a human but, with voice and surveillance. The problem in this is to Sync the 17 degree of freedom (DOF) motors to perform human action’s using voice commands. The humanoid robot is voice controlled with artificial intelligent (Virtual voice assistance AI technology). At first the parts need to be designed as per the human form by fixing each of the joint’s with DOF motors which is in-turn connected to the 18-channel steering servo drive control panel. And we need to program it to perform actions such as walking, waving hand etc. With these feature’s we intend to implement a virtual voice assistance (AI database) to the computer processor as well as surveillance camera to it. The expected result is that, the humanoid robot should perform the action as per the given command, to answer the questions we ask and can surveillance the area around it.